2022
DOI: 10.1002/jmv.27559
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of COVID‐19 laboratory diagnosis by commercial kits: Effectivity of RT‐PCR to the RT‐LAMP

Abstract: Coronavirus disease 2019 or COVID-19 caused by novel coronavirus/severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or 2019-nCoV) is an ongoing pandemic that has emerging global effects and requires rapid and reliable diagnostic testing. Quantitative reverse transcription-polymerase chain reaction (q-RT-PCR) is the gold standard method for SARS-CoV-2 detections. On the other hand, new approaches remedy the diagnosis difficulties gradually. Reverse transcription loopmediated isothermal amplification (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…A nasopharyngeal or oropharyngeal swab followed by quantitative real-time reverse transcriptase-polymerase chain reaction (qRT–PCR) is the standard procedure for diagnosis [ 36 – 40 ]. Some immunochromatography assays and other technologies, such as reverse transcription loop-mediated isothermal amplification (RT-LAMP) [ 41 – 43 ], can be used as complements.…”
Section: Covid-19mentioning
confidence: 99%
“…A nasopharyngeal or oropharyngeal swab followed by quantitative real-time reverse transcriptase-polymerase chain reaction (qRT–PCR) is the standard procedure for diagnosis [ 36 – 40 ]. Some immunochromatography assays and other technologies, such as reverse transcription loop-mediated isothermal amplification (RT-LAMP) [ 41 – 43 ], can be used as complements.…”
Section: Covid-19mentioning
confidence: 99%
“…In October of 2020, Österdahl et al’s investigation of RT-LAMP compared to RT-PCR resulted in a PPV (positive predictive value) of 73% and NPV (negative predictive value) of 80%, meaning both clinical sensitivity and specificity were lower than that of PCR, though the test is especially prone to false positives [ 111 ]. Artik et al also reported high false positives in their LAMP reactions (with a 63% positivity) [ 112 ]. Two groups, Usherwood et al and Pu et al, reported LAMP tests that yielded lower clinical sensitivities, resulting in higher false-negative rates [ 113 , 114 ].…”
Section: Lamp Potentials Disregarded In Covid-19 Testingmentioning
confidence: 99%
“…Moreover, the C-terminal of the S1 subunit (S1 CTD) consists of the receptor-binding domain (RBD) which takes the critical role in recognizing and binding the host receptor as shown in Figue 1. Moreover, S protein also takes an important role in recognizing host range and tissue tropism, alongside being responsible for inducing many of the host immune responses [4,5]. On the other hand, ACE2 receptor plays a crucial role in regulating oxygen/carbon dioxide transfer, commonly found within the respiratory epithelia.…”
Section: Introductionmentioning
confidence: 99%